Curcumin gum Arabic nanoparticles demonstrate potent antioxidant and cytotoxic properties in human cancer cells - Hassani, Abdelkader; Hussain, Siti Aslina; Al-Qubaisi, Mothanna Sadiq; Belfar, Mohamed Lakhder; Belkhalfa, Hakim; Enezei, Hamid Hammad; Zentou, Hamid; Ibrahim, Wisam Nabeel; Doolaanea, Abd Almonem (Tech Science Press, 2021)
The main purpose of the study was to enhance the stability and therapeutic effects of Curcumin (Cur) through nanoformulation with gum Arabic (GA) as a coating agent through an efficient synthetic approach. The antioxidant properties of the developed nanoparticles (Cur/GANPs) were assessed through several in vitro assays, such as β-carotene bleaching activity, DPPH, and nitric oxide scavenging activities in addition to evaluating its inhibitory activity on angiotensin-converting enzyme (ACE). The cytotoxicity of Cur/GANPs was evaluated in vitro using different types of human cancer cells including breast cancer (MCF7, MDA-MB231), liver cancer (HepG2), and colon cancer (HT29) cells. The prepared particles displayed an elliptical shape with a size ranging between 20–260 nm and a potential difference of –15 mV. The Cur/GANPs exhibited significant antioxidant activity compared to free curcumin when using concentrations between 31.5 and 500 µg/mL. The Cur/GANPs also had inhibited the growth of all cancer cell lines in a proportional trend with concentrations used. Hence, the encapsulation with gum Arabic has augmented the antioxidant and anti-neoplastic effects of Curcumin. Therefore, Cur/GANPs may have effective therapeutic properties in diseases attributed to oxidative stress like cancer and hypertension.